Peranan Bimbingan Konseling Terhadap Pembangunan Karakter Dalam Merealisasikan Nilai-Nilai Pancasila - Umamah, Fauziyah Nur; Nurchotimah, Aulia Sholichah Iman (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
The phenomenon of deviations from Pancasila values ​​still frequently occurs in social life, and of course does not reflect an attitude that is in appropriate with values ​​be contained in Pancasila. Among the causes is the lack of awareness of the implementation of Pancasila values ​​which has resulted in the exclusion of the Pancasila ideology. The purpose of this study is to find out how the role of education in building the nation's character in the era of generation z, as well as the implementation of Pancasila values ​​through the perspective of guidance and counseling. The method used in this paper is a literature review study whose writing results focus on the topic or related writing variables. The results of this study indicate that the implementation of every value contained in Pancasila has not been realized properly, the cause is seen from several cases that occurred in Indonesia which showed an imbalance between the values ​​of Pancasila and its actualization which resulted in this needing special attention for the government and citizens. in order to carry out every Pancasila values ​​properly and correctly Keywords: Counseling guidance;Character, Pancasila values